Pengembangan Game Ular Tangga dengan Kartu Baca Untuk Meningkatkan Kemampuan Membaca Permulaan Kelas 2 SD Plosojenar - Shinta Meyza Putri; Anisa Surya Kartika; Erdea Widiyani; Rani Setiawaty (Lembag, 2024)
The aim of this research is to develop and determine the feasibility of learning media in the form of snakes and ladders in class 2 of SD N Plosojenar. This research uses the Borg and Gall model, which is a method or step for creating new products or developing and perfecting existing products. The subjects of this research were 13 grade 2 students at SD N Plosojenar. Data collection techniques include observation, interviews, pre and post test methods, as well as teacher and student responses. The type of data is qualitative and quantitative data which contains evaluation category criteria to determine product suitability. The results of this research are as follows: 1). Snakes and Ladders media was also developed. 2). The teacher's response to snake media was with a score of 4.82. Based on calculations based on the teacher's response, it can be concluded that the snakes and ladders game media is